Service Quality, Product Quality, and Perception of Price for Consumer Satisfaction at Aqiqah Business - Nabilah Zhafirah; Rahayu Relawati; Bambang Yudi Ariadi (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2021)
Consumer Satisfaction is an assessment of the features of a product or service that provides a level of pleasure to customers related to meeting customer consumption needs. Aqiqah Nurul Hayat has been serving aqiqah services since 2003 and already has more than 30 branches spread throughout Indonesia. The purpose of this study was to determine the relationship between price perception, service quality, and product quality to consumer satisfaction with aqiqah Nurul Hayat Malang Branch. The research location is at the office of Nurul Hayat Malang branch on Jl. S. Supriadi No. 7 Sukun. Sampling used the accidental sampling method, the respondents obtained were 73 people. The analytical method used in this study is Spearman's Correlation. The data used are primary data. The results obtained indicate that the perception of price, service quality, and product quality have a relationship with customer satisfaction Aqiqah Nurul Hayat Malang branch. The results of the analysis show that perceived price, service quality, and product quality have a strong relationship with customer satisfaction at the Aqiqah Nurul Hayat Malang branch. The recommendation given is to maintain customer satisfaction by continuing to maintain the quality of both services and products.